Traction electric drive of locomotives with a group drive of wheel pairs - Porada, Andrii (National Technical University "Kharkiv Polytechnic Institute", 2024)
The main goal of fundamental research in the field of electromagnetism and electrodynamics is to improve the theory of synchronous generators used in power stations. The proposed research aims to enhance the efficiency and sustainability of Ukraine's energy sector through innovative hydroelectric power solutions. The study also underscores the importance of addressing technical challenges and optimizing the design of high-voltage hydro generators for integration into Ukraine's energy system. Additionally, the development of high-voltage hydro generators presents opportunities for improved efficiency, reduced environmental impact, and technological advancements to contribute substantially to electricity production.
Keywords: traction electric drive; locomotives; hydro units; hydroelectric power stations; modernization; innovative solutions